A Study on Biometric Technology and Access Control System: Network Security - Lathwal, Reenu; Saroha, Vinod Kumar (International Journal of Computer Sciences and Engineering, 2014)
Biometrics system used in worldwide in nature last few years. Using biometric we can combine with other tools to perform more security function and it is very easier to use verification solutions. It is easy to remember because it based on physiological and behavioral characteristics. In order to avoid problems of forgetting password and ID codes, biometric based authentication helps us in verifying your finger prints, iris pattern and voice for your identity at A.T.M’s, Airports etc…, you can unlock your houses, withdrawing money from a bank with just a blink of an eye, a tap of your finger or by just showing your face. A new technology come under consideration of biometric that is biometric attendance system. This system is very helpful with various patterns like face recognition, iris recognition, fingerprint etc.